Medical biochemistry - Baynes, John W.; Dominiczak, Marek H. (Elsevier Health Sciences, 2019)
"Brought to you in a thorough yet accessible manner, this new edition of Medical Biochemistry highlights the latest developments in regulatory and molecular biology, signal transduction, biochemistry and biomarkers of chronic disease, and bioinformatics and the '-omics'. It highlights the most important global medical issues-including diabetes mellitus, obesity and malnutrition, cancer and atherosclerotic cardiovascular disease-and addresses the role of nutrition and exercise in medicine."